Feeding and Management Strategies of Rearing and Fattening Lambs in Summer in Uruguay: Literature Review - Montossi, Fabio; Cazzuli, Fiorella (Agrociencia Uruguay, 2016)
Among the limiting factors preventing further development of the Uruguayan Sheep Meat Industry, the seasonality of lamb supply is highlighted. The latter is mainly associated with constraints in forage quantity and quality, which usually occurs in summer, followed by autumn. This article summarizes, systematizes and prioritizes research information about lamb rearing and fattening during the summer months, and the eventuality of its extension through autumn. Animal production parameters recorded in research conducted abroad and nationally are summarized. Local information focuses on the study of various factors, such as type of forage base used, grazing systems, level and type of supplementation, use of irrigation, stocking rate, and gender, on lamb productivity. It is concluded that there is a wide range of technology options and recommendations generated by national research, available for technical advisors and farmers, to evaluate the productive and economic convenience of implementing accelerated lamb rearing and fattening systems during summer in Uruguay.